The body and media - Breczko, Sylwia (Body and society. Sociology of the body in research and theoretical concepts, 2023)
Sociology is interested in the media messages concerning the body, assuming that media are one of the basic institutions of socialization through which we learn social norms about the body. The media allows us to go beyond the narrow family circle and local community, confronting us with the global culture and social expectations, which are also very often conditioned by gender. Social ideals about the desired shape have a profound impact, in particular on the generation of young women. This chapter presents key sociological notions, which may be employed to analyse the influence of media on the experience of embodiment. Concepts such as the individualisation of body, consumer culture, symbolic violence and body capital are introduced and the theories of, i.a., Jean Baudrillard, Anthony Giddens, Pierre Bourdieu, and Erving Goffman are discussed. In the research section, the focus is placed on the issues of representativeness of media images and body (self-)surveillance in social media. We analyse the symbolic annihilation occurring in the media and present research concerning how the media under-representation of certain social groups (e.g. the disabled, the sexually non-normative) may result in a falsified worldview. Attention is also paid to the prevalent fat phobia and fat shaming, which influence the body image and the self-esteem of the group that is the most susceptible to media messages, i.e. children and teenagers. The chapter ends with the reconstruction of building bodily self-knowledge on the example of the Polish media during the transformation period.